2010
DOI: 10.1269/jrr.09137
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Biology of Heavy-Ion Cancer Therapy

Abstract: Superb biological effectiveness and dose conformity represent a rationale for heavy-ion therapy, which has thus far achieved good cancer controllability while sparing critical normal organs. Immediately after irradiation, heavy ions produce dense ionization along their trajectories, cause irreparable clustered DNA damage, and alter cellular ultrastructure. These ions, as a consequence, inactivate cells more effectively with less cell-cycle and oxygen dependence than conventional photons. The modes of heavy ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 127 publications
0
95
0
2
Order By: Relevance
“…In addition to improved dose distribution conferred by particle irradiation, a markedly increased efficiency of cell killing is another attractive reason for investigating heavy ions (15). Furthermore, hypoxic cells naturally occur within cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to improved dose distribution conferred by particle irradiation, a markedly increased efficiency of cell killing is another attractive reason for investigating heavy ions (15). Furthermore, hypoxic cells naturally occur within cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies have demonstrated that high LET radiation is more effective than low LET radiation in terms of cell-killing effects (10)(11)(12)(13). Additionally, the extent of cell killing by heavy ions is not cell cycle dependent and is not decreased due to the presence of hypoxia (14)(15)(16). In human oncology, the relative biological effectiveness (RBE) is used to describe the increase in effectiveness of particle radiation (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether in the pimonidazole-unlabelled or the whole Q cell population, it follows that control of the Q cells has a great impact on the outcome of radiation therapy and that the Q cell population can be a critical target in the control of solid tumours. At high-LET carbon ion irradiation, tumour radiosensitivity and the capacity to recover from radiationinduced damage are known to be significantly less dependent on intratumour oxygenation status and the irradiation dose rate [18]. This is thought to be partly because the frequency of closely spaced DNA lesions forming a cluster of DNA damage produced by high-LET carbon ion beams is much less dependent on oxygenation status at the time of irradiation than that of DNA damage produced by low-LET c-ray irradiation [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that HZE particles have a higher (several to many fold greater) relative biological effectiveness (RBE) than X or γ-rays (sparsely ionizing radiation) (2,(18)(19)(20)(21)(22)(23) . Cells exposed to high-LET irradiation exhibit increased relative biological effectiveness of death, chromosomal aberrations, mutagenesis and carcinogenesis (5,14,18,24,25) .…”
Section: The Biological Effects Of Hze Particlementioning
confidence: 99%
“…In addition, the information are pertinent to radiotherapy, as particle therapy with energetic protons or heavy ions (e.g. carbon ions) is increasingly being used in cancer treatment (9,12,13) . Therefore, to understand the mechanisms that underlay the biological effects induced by HZE particle radiation is essential for space exploration and for radiotherapy.…”
Section: Introductionmentioning
confidence: 99%